Fluid restriction in hemodialysis patients with chronic kidney disease in RSUP Dr. Mohammad Hoesin Palembang - Wijayaa, Andi Putra; Septiani, Rina; Sari, Dewi Kartika; Rizky, Ahmad Fauzi; Hidayah, Nurul; Arifin, Zulkarnain (Indonesian Nursing Journal, 2025)
Background: Chronic kidney disease (CKD) patients undergoing hemodialysis must adhere to fluid restrictions to prevent complications such as hypertension, heart failure, and pulmonary edema. However, maintaining adherence is challenging due to physiological, psychological, and social factors. Purpose: This study aims to evaluate compliance with fluid restrictions among hemodialysis patients, identify factors influencing adherence, and propose strategies to improve compliance at RSUP Dr. Mohammad Hoesin Palembang. Methods: A mixed-methods approach was employed, involving a cross-sectional survey of 100 hemodialysis patients and in-depth interviews with 16 participants. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were thematically analyzed. Measures to minimize biases, such as ensuring confidentiality and cross-checking data, were implemented. Results: Quantitative findings revealed that participants had a moderate knowledge score (mean: 7.8/10) and an adherence rate of 75.3%, with a mean interdialytic weight gain of 2.5 kg. Significant correlations were found between knowledge and adherence (r = 0.58, p < 0.001) and adherence and weight gain (r = -0.65, p < 0.001). Qualitative analysis identified themes such as psychological challenges, social influences, coping strategies, and the importance of education. Participants highlighted thirst, cultural expectations, and limited understanding as barriers to adherence, while family support and education emerged as facilitators. Conclusion: Enhancing patient education, addressing psychological and social challenges, and promoting innovative coping strategies are essential to improving adherence to fluid restrictions. Tailored interventions and multidisciplinary approaches can optimize fluid management and patient outcomes in hemodialysis care